2014
DOI: 10.1111/bjh.12753
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre study of primary breast diffuse large B‐cell lymphoma in the rituximab era

Abstract: Summary Primary breast diffuse large B-cell lymphoma (DLBCL) is a rare subtype of non-Hodgkin lymphoma (NHL) with limited data on pathology and outcome. A multicentre retrospective study was undertaken to determine prognostic factors and the incidence of central nervous system (CNS) relapses. Data was retrospectively collected on patients from 8 US academic centres. Only patients with stage I/II disease (involvement of breast and localized lymph nodes) were included. Histologies apart from primary DLBCL were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
121
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(152 citation statements)
references
References 19 publications
24
121
7
Order By: Relevance
“…1,2,7,9,17,18 Accumulated evidence from studies of extranodal involvement have shown that testicular or breast involvement (particularly as primary lymphoma, but also as secondary involvement) is clearly associated with a higher rate of CNS relapse. 5,[19][20][21] A growing body of evidence indicates a higher CNS relapse rate among patients with renal involvement by lymphoma. Villa and colleagues 22 reported CNS involvement in 36% of patients with DLBCL with renal involvement.…”
Section: Guidelines For Diagnosis Prevention and Management Of Centrmentioning
confidence: 99%
“…1,2,7,9,17,18 Accumulated evidence from studies of extranodal involvement have shown that testicular or breast involvement (particularly as primary lymphoma, but also as secondary involvement) is clearly associated with a higher rate of CNS relapse. 5,[19][20][21] A growing body of evidence indicates a higher CNS relapse rate among patients with renal involvement by lymphoma. Villa and colleagues 22 reported CNS involvement in 36% of patients with DLBCL with renal involvement.…”
Section: Guidelines For Diagnosis Prevention and Management Of Centrmentioning
confidence: 99%
“…The natural history of breast lymphoma is known to be different from other extranodal lymphomas, due to its rapid progression and poor prognosis 1 . The diagnosis is made by clinical examination and pathology, and the disease usually occurs in women in their 50s or 60s 4 . The most common symptom is a lump or a palpable, unilateral and painless mass in the breast.…”
Section: Case Descriptionmentioning
confidence: 99%
“…Although rare, there are some reports of bilateral lymphomas 7 . Other diagnoses are made through incidental findings in mammography screening or computed tomography (CT) scans 1,4 . Less frequent symptoms are shrinking or papillary flow, thinning of the skin and swelling, simulating an inflammatory carcinoma and B symptoms (fever, weight loss and sweating), which are more common in patients with secondary origin 1,2,4 .…”
Section: Case Descriptionmentioning
confidence: 99%
“…37 In contrast, the association between primary breast lymphoma and CNS relapse is underappreciated, despite data suggesting crude incidence of 12% to 16%. 17,38,39 Stage IIE disease, 17 stage-modified IPI $ 2, 17 bilateral breast involvement, 40 and tumor . 5 cm 41 have all been observed in individual studies to be potential risk factors for CNS involvement, but the findings have not been consistently replicated.…”
Section: 33mentioning
confidence: 99%
“…A summary of the factors we consider when assessing CNS risk is presented in Table 1. 6,[16][17][18][19][20][21][22][23][24][25][26][27][28][29] Case 1 Presentation. A 78-year-old retired nurse presented with hematemesis.…”
mentioning
confidence: 99%